Improved Student Participation of Mind to Learning Thematic Using Community Technology Science (STM) Science Approach Class IV in Primary Education - Nofriza Efendi; Yanti Fitria; Farida F; Syahniar Syahniar (International Journal of Educational Dynamics, 2019)
This research is motivated because students have not fully participated in the thoughts on thematic learning in class IV SDN 24 Kalumbuk City of Padang . Students have not seen much like expressing opinions, asking questions, and answering questions, in learning activities . This study discusses b agaimanaka h p eningkatan participation mind on thematic learning with use approach science Technology Community (STM) in Class IV SDN 24 Kalumbuk, Padang City